Queijo regional do sudoeste do Paraná durante a maturação: caracterização microbiológica, química e física - Brandielli, Marilde Canton (2016)
The regional cheese which is made exclusively in the southwestern region of Paraná State, with autochthonous lactic culture from milk microorganisms of producers from the region, has the purpose of both marketing and enhancement of dairy products with regional characteristics. This study aimed to evaluate the microbiological, chemical and physical changes of the cheese produced with two indigenous lactic cultures (yeast A and B) of Paraná Southwest region during the maturation process at 0, 60 2120 days. The physicochemical parameters evolved, as expected during maturation, with aw, pH and moisture decreasing and increasing acidity parameters (in lactic acid and fatty acid), total solids, total protein, lipid, fat in dry matter and ashes. S. thermophilus showed the highest score at the start of maturation when compared to the L. delbrueckii sp. bulgaricus and values near the periods 60 and 120 days. The proteolysis (IEP and IPP) increased during maturation. The fatty acid profile showed a higher percentage of palmitic, oleic, stearic and myristic, and various fatty acids showed differences between cheeses at different stages of maturation. The color of regional cheese during maturation has shown a reduction on brightness and on the other hand an increase of green and yellow color. The cheese texture showed decreased cohesion parameters, elasticity and chewiness, and toughness showed no difference during maturation. Cheeses made with yeast A (QA) and B (QB) differ from each other to 0 days to acidity in lactic acid acidity in fatty acids, moisture, total solids, potassium, calcium, IPP, L *, b * and elasticity. At 60 days, the acidity analysis in lactic acid, IEP and S. thermophilus differed between QA and QB and 120 days only the color parameters a * and b *. The linear correlation test for color correlated with water activity, moisture, total solids, lipids, NS pH 4.6 and NS TCA 12% for L * a * coordinate and, as the coordinate b * only correlated to lipids. The texture parameters (cohesion, elasticity and chewiness) correlated with the assessed chemical parameters (water activity, moisture, total solids, protein - except elasticity, lipids, NS pH 4.6, NS TCA 12%). According to the study in the development of regional cheese during maturation, new data has been added especially in the evolution of proteolysis count lactic acid bacteria, fatty acid profile and correlation between chemical parameters, color and texture. It was also observed distinct performance between the two yeasts only at the beginning of the maturation of both cheeses, which will not be marketed at this point.